Estudo comparativo de concretos com agregado graúdo reciclado de telha cerâmica e agregado graúdo natural - Fonseca, Adriana Pinheiro (2006)
The generation of residues and its consequent, correlated impacts has been a concern and has mobilized the technico-scientific field in the search for solutions seeking to make productive activities sustainable. In the productive chain of civil construction the segment of tile production from red ceramics generates residues with no appropriate destination and which, in turn, produces losses to the industry, the public administration and the society. A diagnosis of these residues shows that the generated amount is significant, however there is potential for recycling it in civil construction, which should be investigated. This work reports on both the production of reference concrete with natural aggregates and concrete with partial and total replacement of the large aggregate by the recycled aggregate of ceramic tiles. The recycled aggregate presents significant differences regarding the basaltic large aggregate that was used, with much lower apparent specific mass and much higher absorption of water. The concrete thus produced was compared in the fresh state, controlling for the reduction of the cone log. It was verified that the consumption of water for production of the concrete with recycled aggregate is higher and that it is dependent on the rate of aggregate water absorption. Also, the effective water/cement relation is uncertain. The properties of the hardened state: resistance to compression, resistance to traction, and module of elasticity were also comparatively evaluated. The concrete, with recycled aggregate, presented lower mechanical resistance than the reference concrete. Maintaining the cement consumption and constant workability, the mechanical resistance was superior when using a plasticizer addictive. The same occurred when the water/cement relationship was kept constant with higher cement consumption.